CHEWING GUM: CONFECTIONARY TO A POPULAR TRANSBUCCAL DOSAGE FORM - Jhanwar, Bharat; Tomar, Bhupendra Singh; Verma, Surajpal (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Chewing gum is a highly convenient and controlled release transbuccal drug delivery system taken without water. It is gaining popularity as a selfadministrable carrier for the medication used for motion sickness, smoke cessation, hypertension, xerostomia, dental caries, pain, as nutritive and energy supplements. Functional chewing gum favors both local and systemic effects intended to be chewed about half an hour. It has emerged out with a fast onset of action either by direct absorption or swallowed with saliva into gastrointestinal tract.It has better bioavailability that lowers the doses and reduces the gastric side-effects. Gums adhere with ease and compliance of administration to children and dysphagia patients. Chewing gums are formulated using a water-insoluble gum base with water-soluble excipients with the active ingredient in the case of medicated gums. European Pharmacopeia standards used for release studies, there are no other particular official standards. It has attracted the researchers as successful potential drug delivery system in coming future. The present article reviews it as novel drug delivery system including its merits and limitations, material and methods of formulation and evaluation.